A rare case of cytomegalovirus papillitis in patient with immunodeficiency (Medical Journal of Indonesia, 2016)
A 26-year-old male diagnosed with AIDS came with sudden blurred vision and central sco-toma in left eye since 2 weeks before admission. His visual acuity was counting finger at 5 meters with normal IOP and anterior segment. The posterior segment revealed edematous optic nerve covered by exudates and hemorrhages. Due to low CD4+ count and serological test result, we considered a HIV-related opportunistic ocular infection, specifically HSV infection. As visual acuity worsened during treatment with acyclovir, we performed PCR ex-amination from aqueous tap which revealed positive CMV DNA. Unfortunately, the visual acuity had worsened to no light perception before he received any specific anti-CMV agent. CMV papillitis is an unusual presentation of CMV retinitis. PCR examination from aqueous or vitreous tap should be performed while waiting for serological test result, especially in doubtful cases. Therefore, appropriate diagnosis and management can be established early to prevent irreversible visual loss.